STUDY ON THE SUNFLOWER SEEDS MARKET IN ROMANIA - Elena SOARE; Irina-Adriana CHIURCIU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The present research aims to present and analyze the production and marketing of sunflower seeds in Romania, based on data obtained from the National Institute of Statistics and from the website of the Ministry of Agriculture and Rural Development, for the period 2015-2020. In order to highlight as realistically as possible the production and marketing of sunflower seeds at the national level, it was necessary to analyze the most important quantitative indicators, such as: the total area cultivated with sunflowers; the total production of sunflower seeds; average production of sunflower seeds per hectare; the average price for sunflower seeds on the domestic market; the exports and imports of sunflower seeds related to Romania. The sunflower crop has a particular importance, being spread all over the globe, but in different proportions from one region to another. Sunflower seeds are characterized by superior nutritional value because they contain monosaturated fats, proteins, polysaturated fats, as well as other beneficial elements for the human body. In 2020, Romania ranked first among the sunflower growers and producers in the European Union.